DAMPAK PANDEMI VIRUS CORONA TERHADAP PELAYANAN RUMAH SAKIT DI KOTA MEDAN DITINJAU DARI PERSPEKTIF HUKUM - Dewi Ervina Suryani (Universitas Islam Sumatera Utara, 2021)
The government has poured trillions of budgets as a form of seriousness in handling the coronavirus epidemic which began to plague in Indonesia in the early 2020. The amount of the subsidy funds for the treatment of COVID-19 patients given by the government to hospitals is used by unscrupulous hospitals to reap huge profits by convicting the patients who are suffering from other diseases so that they have the status of Covid-19 patients (not Covid-19, sentenced to Covid-19).This research is a type of normative legal research that conducted by examining library materials or secondary data. The secondary data in the form of primary legal materials, secondary legal materials, and tertiary legal materials used in this study were obtained through books, government publications, internal organization records, reports, journals, up to various sites related to the coronavirus. The secondary data which obtained was then processed using library research data collection techniques (library studies). The study was then analyzed qualitatively through analytical descriptive methods, in order to obtain a general conclusion about the coronavirus.The results showed that the form of legal protection against the determination of the status of covid-19 on the patients of general disease by the hospitals in Medan city was in the form of compensation. This refers to the Law No. 8 of 1999 concerning Consumer Protection and the Law No. 36 of 2009 concerning Health.Keywords: Pandemic Impact, Coronavirus